C-Reactive Protein as a Prognostic Indicator in COVID-19 Patients. (29th April 2021) - Sadeghi-Haddad-Zavareh, Mahmoud; Bayani, Masomeh; Shokri, Mehran; Ebrahimpour, Soheil; Babazadeh, Arefeh; Mehraeen, Rahele; Moudi, Emadoddin; Rostami, Ali; Barary, Mohammad; Hosseini, Akram; Bijani, Ali; Javanian, Mostafa
Abstract : While some biomolecules have been explored to identify potential biomarkers for the prognosis of COVID-19 patients, there is no reliable prognostic indicator of the disease progression and severity. We aimed to evaluate the ability of the C-reactive protein (CRP) to predict COVID-19 infection outcome. This retrospective study was conducted on 429 patients diagnosed with COVID-19 between March 30, 2020, and April 30, 2020. The study population was divided into severe ( n  = 175) and nonsevere cases ( n  = 254). Data on demographic characteristics, clinical features, and laboratory findings on admission were collected. The proportion of patients with increased CRP levels was significantly higher in severe cases than in nonsevere patients. Analysis of the receiver operating characteristic (ROC) curve found that CRP could be used as an independent factor in predicting the severity of COVID-19. Also, patients with CRP >64.75 mg/L were more likely to have severe complications. In conclusion, CRP serum levels can predict the severity and progression of illness in patients with COVID-19.